2020
DOI: 10.3390/cancers12061645
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Targeting Tumor-Initiating Cells Prolong Survival in a Post-Surgery, Post-Chemotherapy Ovarian Cancer Relapse Model

Abstract: Disease recurrence is the major cause of morbidity and mortality of ovarian cancer (OC). In terms of maintenance therapies after platinum-based chemotherapy, PARP inhibitors significantly improve the overall survival of patients with BRCA mutations but is of little benefit to patients without homologous recombination deficiency (HRD). The stem-like tumor-initiating cell (TIC) population within OC tumors are thought to contribute to disease recurrence and chemoresistance. Therefore, there is a need to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 71 publications
5
46
0
Order By: Relevance
“…A Metascape GO tree showed that cell cycle regulation terms cluster together, while metabolism regulation terms also cluster ( Figure 1 C). These data suggest that in addition to altered metabolism and oxidative stress, which we have previously shown support ovarian cancer spheroids [ 27 ], cell cycle regulation plays a critical role in growth in 3-D and may correlate with specific markers of TICs.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A Metascape GO tree showed that cell cycle regulation terms cluster together, while metabolism regulation terms also cluster ( Figure 1 C). These data suggest that in addition to altered metabolism and oxidative stress, which we have previously shown support ovarian cancer spheroids [ 27 ], cell cycle regulation plays a critical role in growth in 3-D and may correlate with specific markers of TICs.…”
Section: Resultssupporting
confidence: 69%
“…We next measured spheroid formation efficiency in 3-D conditions. Spheroids are multicellular tumor cell aggregates that resemble those found in patient ascites, and are often used as an in vitro surrogate to measure tumor-initiation capacity [ 9 , 27 , 31 , 32 ]. All cell lines had relatively equal ability to form spheroids with 3-D media ( Figure 2 C,D).…”
Section: Resultsmentioning
confidence: 99%
“…1C). These data suggest that in addition to altered metabolism and oxidative stress, which we have previously shown to support ovarian cancer spheroids [38], cell cycle regulation pathways play a critical role in supporting growth of ovarian cancer cells in 3-D and may correlate with specific markers of TICs.…”
Section: Resultssupporting
confidence: 59%
“…We previously showed that ovarian cancer cells cultured in 3-D conditions enhances growth of tumor cells as multicellular spheroids and enriches for TICs with elevated expression of stem cell markers, increased tumorinitiating capacity, and greater resistance to chemotherapies [15,25]. Subsequent RNA-sequencing and Gene Set Enrichment Analysis (GSEA) showed an increase in genes involved in drug metabolism and oxidative stress in OV90 cells cultured in 3-D relative to 2-D conditions [38]. A further query of this sequencing data identifies 10,222 significantly differentially expressed genes (DEGs) in the 3-D cultured cells relative to 2-D cultured cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation